2020
DOI: 10.3389/fpsyg.2019.02959
|View full text |Cite
|
Sign up to set email alerts
|

Do Textbooks Matter for Reading Comprehension? A Study in Flemish Primary Education

Abstract: This study assessed whether textbooks affect academic performance and engagement in reading comprehension in primary education in Flanders (Belgium). The data of the Progress in International Reading Literacy Study 2016 and a reassessment of this study in 2018 were used to describe students' learning progress in reading comprehension and evolution in engagement between the fourth and sixth grade. The sample consisted of 3051 students in 98 schools. The averages of students' learning progress and engagement wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…The teachers in our sample try to fix these problems by providing their students with additional practice-not explanation. This might indicate that teachers themselves also lack the knowledge to provide high quality instruction on text structure, as has been reported in many studies outside the Netherlands as well (e.g., Beerwinkle et al, 2018;Dockx et al, 2020;Seifert, 2021;Wijekumar et al, 2019Wijekumar et al, , 2021.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The teachers in our sample try to fix these problems by providing their students with additional practice-not explanation. This might indicate that teachers themselves also lack the knowledge to provide high quality instruction on text structure, as has been reported in many studies outside the Netherlands as well (e.g., Beerwinkle et al, 2018;Dockx et al, 2020;Seifert, 2021;Wijekumar et al, 2019Wijekumar et al, , 2021.…”
Section: Discussionmentioning
confidence: 86%
“…Teaching materials constitute the implemented curriculum, which entails the learning content and instructional approach that teachers offer in their classrooms. Their quality and alignment with government objectives strongly determine effective education (Dockx et al, 2020;Penuel et al, 2014).…”
mentioning
confidence: 99%
“…The latest study tries to test the effectiveness of some textbooks that are applied to grades four to six in elementary school as an effort to progress student learning. The results of the study found that the five textbooks did not affect children's learning progress in reading (Dockx, Bellens, & De Fraine, 2020). South and East African country highlight the lack of evidence on the impact of textbook access on student achievement at the primary school level (Milligan, Tikly, Williams, Vianney & Uworwabayeho, 2017), and the most important gap was the lack of textbook availability in the field of sports and physical education for students (Gazali & Cendra, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…In general education but also in the second language (L2) learning and teaching, materials have been the staple in curricula. Language learning materials refer to texts in all forms including paper, audio, and video as well as predefined language learning tasks (Harwood, 2010) which mediate between the intended and implemented curriculum (Dockx et al, 2020). The processes of arriving at the final materials for language learning programs including design and evaluation along with syllabus design, assessment, and evaluation of instruction establish the core activities in applied linguistics (McGrath, 2002).…”
mentioning
confidence: 99%